Doubles Deceit and Reflexive Narrative in two Novels by Vladimir Nabokov - María Asunción Barreras Gómez (Miscelánea: A Journal of English and American Studies)
Nabokov's novels show that imagination creates its own reality by giving order and meaning to a subject. They do not reflect reality but instead they express their own individual reality. The motif of the Doppelgänger or double is one of the main devices used by Nabokov. It allows the novelist to parody consciously and symmetrically the actions of the characters. It is a recurring design by which the novel refers to itself. The heroes of both Despair and Lolita describe their relationship with their double and his murder. However, the reader is never sure whether the story of the double is true or whether the doubles are in fact just part of the protagonists' imagination. The reader has to decide whether the story is true or not. This is a metafictional feature. The reader creates the novel as well, when he decides what to believe. Both novels remind the reader that fiction is an illusion, and not the reality it may seem.